Distinct mechanisms of regulation of the ITGA6 and ITGB4 genes by RUNX1 in myeloid cells. Issue 4 (14th November 2017) - Phillips, Jessica L.; Taberlay, Phillippa C.; Woodworth, Alexandra M.; Hardy, Kristine; Brettingham‐Moore, Kate H.; Dickinson, Joanne L.; Holloway, Adele F.
Abstract : Integrins are transmembrane adhesion receptors that play an important role in hematopoiesis by facilitating interactions between hematopoietic cells and extracellular matrix components of the bone marrow and hematopoietic tissues. These interactions are important in regulating the function, proliferation, and differentiation of hematopoietic cells, as well as their homing and mobilization in the bone marrow. Not surprisingly altered expression and function of integrins plays a key role in the development and progression of cancer including leukemias. However, the regulation of integrin gene expression is not well characterized and the mechanisms by which integrin genes are disrupted in cancer remain unclear. Here we demonstrate for the first time that a key regulator of hematopoiesis, RUNX1, binds to and regulates the promoters of both the ITGA6 and ITGB4 genes in myeloid cells. The ITGA6 and ITGB4 integrin genes form the α6β4 integrin receptor. However, our data indicate that RUNX1 functions differently at these two promoters. RUNX1 regulates ITGA6 through a consensus RUNX1 binding motif in its promoter. In contrast, although the ITGB4 promoter is also activated by RUNX1, it does so in the absence of a recognized consensus RUNX1 binding motif. Furthermore, our data suggest that regulation of ITGB4 may involve interactions between the promoter and upstream regulatory elements. Abstract : Integrins play an important role in hematopoiesis, and not surprisingly their altered expression plays a key role in the development and progression of cancer, including leukemia. RUNX1, a key transcriptional regulator of hematopoiesis, regulates the ITGB4 and ITGA6 integrin genes, which together form the α6β4 integrin receptor.